ILLOCUTIONARY ACTS USED IN THE DISNEY MOVIE THE GOOD DINOSAUR - Loi, Anis Elvina (Universitas Nias Raya, 2025)
This study aimed at finding the types of illocutionary acts and describing the meaning of illocutionary act used in the movie The Good Dinosaur. This study used the theory of Searle (1998). This research used descriptive qualitative method and the data collection method was documentation. The object of this research was all conversations in the movie The Good Dinosaur that contain types of illocutionary acts. The result of this research, was were 52 utterances as illocutionary acts. There were four types of illocutionary acts found in the movie namely: 19 assertives, 17 directives, 8 commissives, and 8 expressives. There was also found that each utterance of illocutionary act had the different meanings based on the context of the story. From the results of this study, it can be seen that illocutionary acts are widely used in daily life. Therefore, understanding the meaning of illocutionary acts is very important for smooth communication. It is hoped that this research can help English teachers to be able to improve their ability to communicate effectively and understand other cultures so that they can teach students how to use appropriate language, as well as English language learners to be able to better understand the context in speaking.